2010
DOI: 10.1161/circgenetics.110.957415
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNA-208b and MicroRNA-499 Reflect Myocardial Damage in Cardiovascular Disease

Abstract: Background-Small RNA molecules, called microRNAs, freely circulate in human plasma and correlate with varying pathologies. In this study, we explored their diagnostic potential in a selection of prevalent cardiovascular disorders. Methods and Results-MicroRNAs were isolated from plasmas from well-characterized patients with varying degrees of cardiac damage: (1) acute myocardial infarction, (2) viral myocarditis, (3) diastolic dysfunction, and (4) acute heart failure. Plasma levels of selected microRNAs, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
606
8
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 719 publications
(649 citation statements)
references
References 32 publications
26
606
8
9
Order By: Relevance
“…Increases in circulating miRNAs upon cell damage have been detected by RT-PCR-based approaches for liver, brain, and skeletal muscle (5), as well as heart (19,46 instances miRNAs even performed better than established protein biomarkers (5). Our analysis indicated that heart-specific myomirs performed similar to the highly sensitive cTnI assay, but we were unable to verify the utility of any recently proposed miRNA biomarker for HF (18,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in circulating miRNAs upon cell damage have been detected by RT-PCR-based approaches for liver, brain, and skeletal muscle (5), as well as heart (19,46 instances miRNAs even performed better than established protein biomarkers (5). Our analysis indicated that heart-specific myomirs performed similar to the highly sensitive cTnI assay, but we were unable to verify the utility of any recently proposed miRNA biomarker for HF (18,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…S1) were shown to contribute to muscle or myocardial function (8, 9). miRNAs and other classes of RNA have been profiled in failing human myocardium (10)(11)(12)(13)(14)(15)(16)(17), and a selected subset was also investigated as circulating biomarkers in HF (18)(19)(20)(21)(22)(23)(24). However, in these studies heart tissue and circulating miRNA abundance changes were not acquired simultaneously to correlate changes in tissue versus circulating miRNA composition.…”
mentioning
confidence: 99%
“…However, leukocyte specific miRNAs were not increased in significant amount [60]. Further to this, the role of miR-499 in AMI diagnosis has been supported by Adachi et al in which they measured the plasma concentration of miR-499 in 14 patients with acute coronary syndrome, 15 patients with congestive heart failure (CHF) and 10 patients without any cardiovascular disease.…”
Section: S Pokhrel Y Guotian World Journal Of Cardiovascular Diseasesmentioning
confidence: 87%
“…There was an increase of more than 1,000-fold in acute myocardial infarction 6,[37][38][39] of miRs-208b and-499. In this condition, they reflect tissue injury and cell death.…”
Section: Microrna As Biomarker In Heart Failurementioning
confidence: 96%